APOLIPOPROTEIN A1 GENE AND ITS ROLE IN DYSLIPIDEMIA DEVELOPMENT ACROSS ETHNIC GROUPS OF PATIENTS WITH ESSENTIAL ARTERIAL HYPERTENSION - T. A. Bairova; V. V. Dolgikh; L. I. Kolesnikova; D. M. Munkoeva (Российский кардиологический журнал)
Aim. To assess the impact of insertion-deletion polymorphism of apolipoprotein A gene on the development of dyslipidemia among adolescents with essential arterial hypertension (EAH), in regard to the ethnic group: non-indigenous Slavic vs. indigenous Buryat. Material and methods. In total, 399 adolescents were examined: 226 patients with the verified EAH diagnosis and 173 controls. Among EAH patients, 144 adolescents (63,7%) were from the non-indigenous ethnic group, while 82 (36,3%) were from the indigenous one; among controls, the respective figures were 94 (53,4%) and 79 (45,7%). Dyslipidemia was diagnosed using the unified criteria. For genetic analyses, total DNA was extracted from venous blood samples, using a non-enzymatic method. DNA fragments were amplified in the polymerase chain reaction (PCR), using the reagent kit “SNP express” according to the producer’s protocol (Litech, Moscow). Results. The deletion allele prevalence in adolescents from the indigenous ethnic group was 8,2% among controls and 8,0% among EAH patients (p=1,000). In the non-indigenous ethnic group, the respective figures were 7,9% and 9,8% (p=0,493). According to the multivariate analysis results, lipid levels in non-indigenous carriers of various insertion-deletion ApoA1 genotypes could be predicted as follows: triglyceride (TG) levels = 1,552 + (-0,653 ApoA1 (II); model F=7,174, p=0,009;  R2=9,4%; very low-density lipoprotein cholesterol (VLD-CH) levels = 0,613 + (-0,189 ApoA1 (II)); model F=4,738, p=0,033; R2=6,3%. Among indigenous patients – carriers of various insertion/deletion ApoA1 genotypes, this polymorphism did not appear to have a significant impact on lipid metabolism parameters. Conclusion. The genome impact on clinical and biochemical phenotype is variable and differs across ethnic groups. Multivariate analyses have demonstrated that TG and VLD-CH levels are associated with the insertion/deletion ApoA1 gene polymorphism. Therefore, this genetic marker could be regarded as a “modifier” gene which determines biochemical polymorphism in non-indigenous patients. In adolescents from the indigenous ethnic group, this molecular and genetic marker appeared irrelevant.